Synthesis of biodiesel using the Mg/Al/Zn hydrotalcite/SBA-15 nanocomposite catalyst - Prabu, Marimuthu; Manikandan, Marimuthu; Kandasamy, Prabu; Kalaivani, P. R.; Rajendiran, Nagappan; Raja, Thirumalaiswamy (Acs Omega, 2019)
Biodiesel production is an enchanting and eccentric pathway for the reduction of use of fossil fuels and is procured from biologically available renewable sources such as oils and fats. A novel Mg/Al/Zn-based hydrotalcite/SBA-15 composite material having a high catalytic activity was developed and investigated for the transesterification of vegetable oil. The rationally developed composites were systematically characterized and assessed in the transesterification of soybean oil in the presence of methanol. The physicochemical evaluation of the nanocomposites demonstrated the influence of Zn in the textural characteristics, density of the basic sites, and successively the catalytic activity. The catalytic efficiency of the MAZ-x/SBA-15 composite could be linked with the basic site density determined by the temperature-programmed desorption of CO2. Among all the composites used, the MAZ-1/SBA-15 nanocomposite showed the highest activity for biodiesels, with a yield of around 90% under economical reaction conditions. The catalytic studies conferred that the fatty acid methyl ester yield is significantly influenced by various experimental conditions such as the catalyst molar ratio, reaction temperature, pressure, and contact time. It was also found that the incorporation of hydrotalcite into SBA-15 pore channels can enhance the catalyst efficiency and stability of the nanocomposite. Moreover, under mild reaction conditions, a remarkably stable catalytic performance was achieved for more than 200 h of time on stream with no catalyst deactivation.

Insights into the catalytic activity of Ru/NaY catalysts for efficient H-2 production through aqueous phase reforming - Gogoi, Pranjal; Nagpure, Atul S.; Kandasamy, Prabu; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (Sustainable Energy & Fuels, 2020)
Ruthenium nanoparticles supported on NaY zeolite catalysts were synthesized by a simple ion exchange method. The structural and morphological features of the catalysts were systematically investigated using numerous techniques such as N-2-sorption, XRD, CO2-TPD, H-2-TPR, TEM, SEM, ICP-OES, TGA, CHN analysis, XPS, in situ CO-FTIR and NMR spectroscopy. These novel Ru-NaY catalysts were highly active and selective for H-2 production through aqueous phase reforming (APR) of glycerol and ethylene glycol. Among the various catalysts evaluated for H-2 production, the 3 wt% Ru-NaY catalyst demonstrated the highest catalytic performance with excellent H-2 selectivity and this catalyst exhibits better activity as compared to many state of the art catalysts reported so far. The superior catalytic activity of 3 wt% Ru-NaY was attributed to the appropriate Ru metal loading, good metal dispersion, small size of Ru nanoparticles, better metal-support interaction, and higher availability of catalytically active sites (Ru-0) and facilitated water gas shift (WGS) reaction. This catalytic activity result clearly shows that NaY zeolite supported Ru nanoparticles catalysts have excellent potential for H-2 production from biomass-derived compounds.

Highly efficient and reusable Ru-NaY catalyst for the base free oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic acid - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy (Catalysis Today, 2021)
Oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is an important reaction for the production of recyclable bio-based polymers. Herein, we report a series of Ru nanoparticles supported on NaY zeolites catalysts for the oxidation of HMF to FDCA. The catalysts were prepared by simple ion exchanged method. Among all the catalysts, the optimized 3 wt % Ru-NaY catalyst showed superior catalytic activity under base free conditions with a shorter period of reaction time. The conversion of HMF was 100 % with 94 % FDCA yield. This catalyst was reused for fourth cycles, with an insignificant decrease in the yield of FDCA. H2-chemisorption and HRTEM studies confirmed that high metal dispersion and small size of Ru nanoparticles play vital roles for the HMF oxidation. In addition, the acidic hydroxyl groups of the supercage as well as higher amount of metallic Ru° are also responsible for the high yield and productivity of FDCA.

Promoted mesoporous Fe-alumina catalysts for the non-oxidative dehydrogenation of isobutane - Venugopalan, Aswathy Thareparambil; Kandasamy, Prabu; Gupta, Nikitra Nihalchand; Thirumalaiswamy, Raja (Catalysis Communications, 2021)
Production of isobutene is commercially consequential and highly demanding from the end-use industries being a key platform molecule as well as an intermediate for a variety of value-added chemicals. Traditionally, isobutene is prepared via steam cracking and fluid catalytic cracking methods. However, the catalysts used in these conventional methods have disadvantages like coke formation, sintering, etc. In this study, the catalytic non-oxidative dehydrogenation of isobutane over acidic, alkaline, and noble metal promoted mesoporous iron-doped catalysts was investigated. Iron doping has a significant function in controlling isobutene selectivity. The synthesis method is crucial to achieve successful metal doping in the mesoporous alumina matrix. Promoted catalysts exhibited a notable difference in isobutane conversion with a marginal change in dehydrogenation selectivity. Silver promoted catalyst showed slightly higher isobutene yield due to the optimal catalytic properties. This catalyst was stable for a considerable duration, and coke deposition, as well as particle agglomeration, were observed to faintly inhibit the catalytic activity.
Keywords: iron; Isobutane; Isobutene; Mesoporous alumina; Non-oxidative dehydrogenation

Utilizing the oxygen carrier property of cerium iron oxide for the low-temperature synthesis of 1,3-butadiene from 1-butene - Venugopalan, Aswathy T.; Kandasamy, Prabu; Gogoi, Pranjal; Ratneshkumar, Jha; Thirumalaiswamy, Raja (Catalysis Letters, 2021)
Low-temperature oxidative dehydrogenation (ODH) of 1-butene to 1,3-butadiene is one of the challenging reactions in the polymer industry. Towards this a highly dispersed cerium iron oxide was synthesized by citrate gel combustion method and employed for the synthesis of 1,3-butadiene (BD) from 1-butene. The reaction was carried out at low temperature under an oxygen-free atmosphere in a continuous flow mode fixed bed reactor. A decrease in the lattice parameters observed from PXRD and high-resolution TEM analysis proved that iron occupies cerium sites in the crystal lattice. XPS, TPR, and oxygen uptake studies quantified the nature and abundance of different oxygen species. ODH was observed through consuming lattice oxygens. The vacancies generated could be filled by re-oxidation with an external supply of oxygen which will restore the catalytic activity demonstrating the Mars van Krevelen mechanism. [GRAPHICS] .
Keywords: 1; 1-butene; 3-butadiene; Cerium; iron; Lattice oxygen; oxidative dehydrogenation

Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst - Gurrala, L.; Kumar, M. M.; Yerrayya, Attada; Kandasamy, Prabu; Castano, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R. (Bioresource Technology, 2022)
The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd-0 and Al2O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (similar to 57 wt%) was obtained at 240 degrees C, 3 h and 3 MPa H-2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted similar to 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of C-alpha=C-beta is proved to occur over the Pd site, while dehydroxylation of C-gamma-OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.
Keywords: Hydrogenolysis; lignin; Mechanism; Pd-Al/activated biochar; Propanol guaiacol; Propyl guaiacol

New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.

Enhancing Ru dispersion and catalytic stability via nitrogen-doped mesoporous carbon supports for biomass-derived FDCA production - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Pandey, Pragati; Raja, Abhishekram; Manikandan, Marimuthu; Raja, Thirumalaiswamy (Inorganic Chemistry Communications, 2026)
The rational design of efficient and selective nanostructured catalysts represents a key strategy for transforming biomass-derived feedstocks into value-added chemicals and fuels. 5-hydroxymethylfurfural (HMF) has emerged as one of the most promising platform chemicals due to its versatile reactivity and potential to be transformed into a wide range of value-added products. Herein, we report the preparation of Ru nanoparticles supported on both N-free and N-doped mesoporous carbon via wetness impregnation, and their application in the catalytic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) under mild reaction conditions. The 3wt% Ru-NMC-2 catalyst afforded complete HMF conversion with 83% yield of FDCA at 110 degrees C within 10 h under 10 bar O2. Our research reveals that the nitrogen content in the carbon matrix imparts basicity to the catalyst support, stabilizing smaller Ru metal nanoparticles and helping to maintain a higher metal dispersion (66%), thereby enhancing FDCA yield and turnover frequency. Furthermore, XPS analysis demonstrated that N doping in the carbon matrix would aid in stabilizing the higher availability of metallic Ru compared with nitrogen-free counterparts. The recyclability of the catalyst was demonstrated over 5 cycles, and it exhibited satisfactory catalytic performance towards FDCA yield.
Keywords: 5-Furandicarboxylic acid (FDCA); 5-hydroxymethylfurfural (HMF); biomass valorization; Metal-support interactions; nitrogen-doped carbon; Ruthenium catalysts